2019
DOI: 10.1371/journal.pone.0219435
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function and dynamics in acyl carrier proteins

Abstract: Carrier proteins are four-helix bundles that covalently hold metabolites and secondary metabolites, such as fatty acids, polyketides and non-ribosomal peptides. These proteins mediate the production of many pharmaceutically important compounds including antibiotics and anticancer agents. Acyl carrier proteins (ACPs) can be found as part of a multi-domain polypeptide (Type I ACPs), or as part of a multiprotein complex (Type II). Here, the main focus is on ACP2 and ACP3, domains from the type I trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…For example, recent studies have demonstrated that engineering enzyme specificity for a non-native AcpP-dependent enzyme can be accomplished by modifying the PPI residues for improved binding 25 . Even single atom changes in the identity of AcpP-bound cargo have been demonstrated to impart perturbations to the structure of acyl-AcpP 26 , 27 .
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies have demonstrated that engineering enzyme specificity for a non-native AcpP-dependent enzyme can be accomplished by modifying the PPI residues for improved binding 25 . Even single atom changes in the identity of AcpP-bound cargo have been demonstrated to impart perturbations to the structure of acyl-AcpP 26 , 27 .
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Tsai et al. recently developed a force field to model the Ppant arm and Ppant-bound intermediates, starter units, and extender units ( 83 , 87 ). Together, these advances provide an exciting framework for applying force fields capable of modeling ACPs in their holo - and acyl -states.…”
Section: Provides a Route To Computationally Simulate Type II Pks mentioning
confidence: 99%
“…Recent progress toward the parameterization of the Ppant arm and its cargo has paved the way for a new era of type II PKS ACP research in which MD simulations can be used hand-in-hand with structural and biochemical approaches. Tsai et al recently developed a force field to model the Ppant arm and Ppant-bound intermediates, starter units, and extender units (83,87). Together, these advances provide an exciting framework for applying force fields capable of modeling ACPs in their holoand acyl-states.…”
Section: Provides a Route To Computationally Simulate Type II Pks Acp Conformations And Interactionsmentioning
confidence: 99%
“…Acyl carrier proteins (ACPs) are a group of structurally homologous proteins found in fatty acid synthases (FASs), polyketide synthases (PKSs) and non-ribosomal peptide synthetases (NRPSs). [32][33][34][35] Comprised of four alpha-helices, their function is to tether and transfer the growing natural product intermediate between enzymatic domains via a phosphopantetheine moiety, which is post-translationally appended to a conserved serine residue on the ACP. Although ACPs are structurally homologous, they have low sequence similarity, even within related biosynthetic pathways.…”
Section: Introductionmentioning
confidence: 99%